Negative electrode material, preparation method thereof and battery

By using secondary granulation technology in aqueous zinc-based batteries to combine zinc oxide primary particles, carbon materials and metal/metal oxides to form micron-scale secondary particles, the problem of corrosion and deformation passivation of zinc-based negative electrode during charging and discharge is solved, and the electrochemical performance and cycle stability of the battery are significantly improved.

CN119542407APending Publication Date: 2025-02-28HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311136879.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In aqueous zinc-based batteries, zinc-based negative electrodes are prone to corrosion and hydrogen analysis, deformation passivation and dendrite growth during storage and charging and discharging, resulting in poor electrochemical performance.

Method used

Through secondary granulation technology, zinc oxide primary particles are combined with carbon materials and metal/metal oxides to form micron-scale secondary particles, and the combination of physical domain confinement and chemical inhibition is used to alleviate the side reaction of zinc-based negative electrode.

Benefits of technology

Effectively inhibit corrosion, hydrogen analysis and deformation passivation of zinc-based negative electrodes, improve the electrochemical performance of the battery, enhance the compaction density of the negative electrode sheet and the load of the negative electrode material, and improve the circulation performance and capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542407A_ABST
    Figure CN119542407A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a negative electrode material, the negative electrode material comprises secondary particles, and the secondary particles comprise a plurality of stacked zinc oxide primary particles, a carbon material dispersed and distributed in the secondary particles, and metal and / or metal oxide. According to the negative electrode material provided by the embodiment of the invention, the zinc oxide, the carbon material and the metal and / or the metal oxide in the secondary particles are uniformly distributed, and the secondary particles can better relieve surface corrosion hydrogen evolution and deformation passivation of a zinc-based negative electrode in the storage and charge-discharge processes in a manner of combining physical confinement and chemical inhibition; the negative electrode material is used for the water-based zinc-based battery, and the electrochemical performance of the water-based zinc-based battery can be improved. The embodiment of the invention also provides a preparation method of the negative electrode material and a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of secondary batteries, and in particular to negative electrode materials, preparation methods thereof, and batteries. Background Art

[0002] Considering safety, cost, environmental protection, high performance and other factors, aqueous rechargeable zinc batteries will become one of the important technologies for the next generation of safe energy storage systems, especially data center UPS (Uninterruptible Power Supply), site energy, and large-scale energy storage. Among them, among aqueous zinc-based batteries, alkaline Ni-Zn battery technology is more mature, and has the highest operating voltage, stable charge and discharge curve, excellent energy density and high rate performance, and has good prospects for large-scale application.

[0003] The commonly used positive electrode material for alkaline Ni-Zn batteries is Ni(OH) 2 The negative electrode material is a Zn / ZnO mixture or a Zn-based material such as calcium zincate. Since the electrolyte is a high concentration (6-7 mol / L) KOH solution, and the Zn-based negative electrode undergoes a solid-liquid-solid phase (Zn-[Zn(OH) 4 ] 2- -ZnO), so the Zn-based negative electrode will inevitably have problems such as corrosion and hydrogen evolution, deformation passivation, and dendrite growth during storage and charge and discharge. In order to alleviate the side reactions of the Zn negative electrode, the industry currently usually performs surface modification or doping modification on the zinc negative electrode. Among them, surface coating can reduce the contact between the active material and the electrolyte, improve the problems of zinc negative electrode dendrites and electrode deformation, but most of the current coating strategies use physical confinement to confine the zinc negative electrode to the shell, but the blocking effect on the hydroxyl zinc ions generated during the reaction is very small, and the inhibitory effect on dendrites and corrosion hydrogen evolution is limited. The structure is usually loose and the tap density is low, making it difficult to achieve low compaction density and high loading of the electrode. In addition to surface coating and modification of the zinc negative electrode, adding a metal or metal oxide with a high hydrogen evolution overpotential to the negative electrode main material to inhibit hydrogen evolution and gas production is another common solution strategy, but simple mechanical addition can easily cause the additives dispersed on the surface of the negative electrode to aggregate and deposit at the bottom during the cycle, losing the protective effect on the upper part of the electrode sheet. Summary of the invention

[0004] In view of this, an embodiment of the present application provides a negative electrode material, which effectively alleviates the corrosion, hydrogen evolution and deformation passivation on the surface of the zinc-based negative electrode during storage and charging and discharging by combining physical confinement and chemical inhibition through secondary granulation. The negative electrode material is used in aqueous zinc-based batteries to improve the electrochemical performance of aqueous zinc-based batteries.

[0005] A first aspect of an embodiment of the present application provides a negative electrode material, specifically a zinc-based negative electrode material, wherein the zinc-based negative electrode material includes secondary particles, wherein the secondary particles include a plurality of stacked zinc oxide primary particles, and carbon materials dispersed in the secondary particles, and metals and / or metal oxides, wherein the metals include one or more of Bi (bismuth), Cu (copper), Sb (antimony), Sn (tin), Ag (silver), and In (indium), and the metal oxides include one or more of Bi oxides, Cu oxides, Sb oxides, Sn oxides, Ag oxides, and In oxides.

[0006] The zinc-based negative electrode material provided in the embodiment of the present application is formed by secondary granulation of zinc oxide primary particles with carbon materials, and metals and / or metal oxides to form micron-sized secondary particles, in which zinc oxide, carbon materials, and metals and / or metal oxides are uniformly distributed, wherein the carbon material can not only improve the conductivity of the zinc-based negative electrode material, but also improve the compactness of the secondary particles and improve the structural stability of the secondary particles; the metal and metal oxide can effectively inhibit hydrogen evolution; the zinc-based negative electrode material is better alleviated by the combination of physical confinement and chemical inhibition through secondary granulation, and the corrosion, hydrogen evolution and deformation passivation of the surface of the zinc-based negative electrode during storage and charge and discharge processes; the zinc-based negative electrode material is used in aqueous zinc-based batteries, and the electrochemical performance of aqueous zinc-based batteries can be improved.

[0007] In the embodiment of the present application, the carbon material and the metal and / or metal oxide are dispersed throughout the secondary particles. That is, in any local position of the secondary particles, the carbon material and the metal and / or metal oxide are dispersed, rather than concentrated in a certain part of the secondary particles in a specific manner. In other words, in the entire secondary particles, the zinc oxide primary particles, the carbon material, and the metal and / or metal oxide are randomly mixed and distributed.

[0008] In the embodiment of the present application, the metal includes one or more of Bi, Cu, Sb, Sn, Ag, and In; the metal oxide includes one or more of Bi oxide, Cu oxide, Sb oxide, Sn oxide, Ag oxide, and In oxide. The above-mentioned types of metals have a high hydrogen evolution overpotential, so that the corrosion and hydrogen evolution of the zinc negative electrode can be better suppressed. In the embodiment of the present application, the secondary particles may include only metals, only metal oxides, or both metals and metal oxides.

[0009] In the embodiment of the present application, in the secondary particles, the mass proportion of the plurality of zinc oxide primary particles is greater than 85%, and the total mass proportion of the carbon material, metal and metal oxide is less than 10%. In the secondary particles, zinc oxide is the main material, and the carbon material, metal and metal oxide are used as auxiliary materials to improve performance. The addition of carbon material can improve the structural stability of the secondary particles by limiting the effect inside the secondary particles, and can also improve the conductivity of the secondary particles. The total mass proportion of carbon material, metal and metal oxide is controlled to be less than 10%, which can better ensure that the zinc negative electrode has a higher gram capacity.

[0010] In the embodiment of the present application, the particle size D50 of the zinc oxide primary particles is 20nm-500nm. The zinc oxide primary particles have a smaller particle size, which is conducive to densely stacking into secondary particles.

[0011] In the embodiment of the present application, the secondary particles further contain a binder. In the present application, the binder can be one or more of sodium carboxymethyl cellulose CMC, polyvinyl alcohol PVA, cellulose, sodium polyacrylate, polyacrylic acid, and sodium alginate. The addition of the binder is conducive to strengthening the bonding between different components in the secondary particles, reducing the porosity of the secondary particles, and increasing the gram capacity of the secondary particles.

[0012] In the embodiment of the present application, in the secondary particles, the mass of the binder is less than 3% of the mass of the zinc oxide. The addition of an appropriate amount of binder can better bind the zinc oxide primary particles, carbon materials, metals and metal oxides together tightly, and is conducive to ensuring that the secondary particles have a higher capacity.

[0013] In the embodiment of the present application, the secondary particles are spherical or quasi-spherical particles. Spherical or quasi-spherical particles have a compact structure and can increase the tap density.

[0014] In the embodiment of the present application, the particle size D50 of the secondary particles is 2 μm-20 μm. Secondary particles of suitable micron size are conducive to obtaining a suitable specific surface area and ensuring that the negative electrode sheet has a large compaction density.

[0015] In the embodiment of the present application, the zinc oxide primary particles are tightly combined with the carbon material, metal and / or metal oxide, and the pores in the secondary particles are all less than 5 nm in diameter. The tightly packed secondary particles and small pore diameter can make the prepared battery negative electrode sheet have a high compaction density and a high active material loading, thereby increasing the battery capacity and the volume energy density of the battery, thereby facilitating the battery to achieve a smaller size design.

[0016] In the embodiment of the present application, the specific surface area of ​​the secondary particles is less than 5m 2 / g. The smaller specific surface area of ​​the secondary particles is beneficial to alleviate the excessive side reaction between the material particle surface and the electrolyte.

[0017] In the embodiment of the present application, the specific surface area of ​​the zinc oxide primary particles is about 20 m 2 / g.

[0018] In the embodiment of the present application, the porosity of the secondary particles is less than 35%. The secondary particles with smaller porosity are beneficial to improving the compaction density and negative electrode material loading of the battery negative electrode sheet, thereby improving the capacity of the battery.

[0019] In the embodiment of the present application, the tap density of the secondary particles is 1.3 g / cm 3 -2.0g / cm 3 The secondary particles have a higher tap density, which can increase the active material loading of the battery negative electrode and improve the battery capacity.

[0020] The zinc-based negative electrode material provided in the embodiment of the present application can be used in a battery system, such as an aqueous zinc-based battery, to improve the electrochemical performance of the aqueous zinc-based battery; it can also be used in the field of photocatalytic hydrogen production from water, the field of solar cell heterojunction diode materials, etc. If applied to the field of photocatalytic hydrogen production from water, the zinc-based negative electrode material may be mixed with other semiconductor materials (such as titanium dioxide, etc.) as an additive, and a hydrogen evolution catalyst may be added to construct a composite electrode material; if used to prepare a diode material, the material may be processed and modified, and a heterojunction diode may be constructed using an n-type ZnO material and a p-type semiconductor material.

[0021] A second aspect of the present application provides a method for preparing a zinc-based negative electrode material, comprising:

[0022] mixing a carbon source, a soluble metal salt, zinc oxide primary particles and water to obtain a solid-liquid mixture;

[0023] The solid-liquid mixture is spray-dried and granulated, and then calcined under a protective atmosphere to obtain a zinc-based negative electrode material; the zinc-based negative electrode material includes secondary particles, the secondary particles include a plurality of stacked zinc oxide primary particles, and carbon materials and metals and / or metal oxides dispersed in the secondary particles.

[0024] The preparation method of the embodiment of the present application sprays and granulates a solid-liquid mixture containing a carbon source, a soluble metal salt and zinc oxide primary particles, and obtains secondary particles after calcination. The zinc oxide primary particles, carbon materials and metal particles are evenly dispersed and tightly combined in the secondary particles, thereby effectively inhibiting corrosion, hydrogen evolution and deformation passivation on the surface of the zinc-based negative electrode during storage and charging and discharging, increasing the compaction density of the negative electrode sheet, and thus improving the battery cycle performance and capacity; and the confinement effect of the carbon material in the secondary particles can improve the overall structural stability of the secondary particles; the preparation method is simple and controllable, and can be used for large-scale production.

[0025] In the embodiment of the present application, the carbon source includes one or more of glucose, starch, sucrose, and citric acid. The above organic carbon sources are simple and easy to obtain, and are easy to achieve complete carbonization.

[0026] In the embodiment of the present application, the soluble metal salt includes one or more of sulfate, nitrate, chloride and acetate. The above soluble metal salts are easily available and easily soluble in water.

[0027] In the embodiment of the present application, the particle size D50 of the zinc oxide primary particles is 20nm-300nm. The zinc oxide primary particles have a smaller particle size, which is conducive to densely stacking into secondary particles.

[0028] In the embodiment of the present application, the solid-liquid ratio in the solid-liquid mixture is 1: (2-5) kg / L. The proper control of the solid-liquid ratio is beneficial to controlling the viscosity of the solid-liquid mixture and is beneficial to preparing compact secondary particles in the subsequent spray drying process.

[0029] In the embodiment of the present application, the inlet air temperature of the spray drying is 170°C-220°C, and the feed rate is 5mL / min-20mL / min.

[0030] In the embodiment of the present application, the calcination temperature is 400°C-1000°C.

[0031] In the embodiment of the present application, the zinc oxide primary particles can be prepared by the following method:

[0032] A zinc oxide precursor is prepared by using a soluble zinc metal salt and an alkali by a precipitation method, and primary zinc oxide particles are obtained after calcination.

[0033] The alkali can be a mixture of one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide. The stoichiometric ratio of the zinc metal soluble salt and the alkali is 1.8-2.2:1, and the pH after mixing is 7-11; wherein the reaction temperature of the precipitation method is 40°C-80°C, and the reaction time is 0.1h-6h.

[0034] A third aspect of an embodiment of the present application provides a battery negative electrode sheet, the battery negative electrode sheet comprising a current collector and a negative electrode active layer disposed on the current collector, the negative electrode active layer comprising the zinc-based negative electrode material described in the first aspect of the embodiment of the present application.

[0035] In the embodiment of the present application, the compaction density of the negative electrode sheet is greater than or equal to 3.8 g / cm 3 The zinc-based negative electrode material loading of the negative electrode sheet is greater than or equal to 115 mg / cm 2 The negative electrode sheet of the battery in the embodiment of the present application adopts the zinc-based negative electrode material provided above, and has a high compaction density and a high zinc-based negative electrode material loading, which can ensure the high energy density of the battery.

[0036] A fourth aspect of an embodiment of the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet comprises the battery negative electrode sheet described in the third aspect of the embodiment of the present application.

[0037] In the embodiment of the present application, the battery includes a zinc-based battery, a lithium-ion battery or a sodium-ion battery. The zinc-based negative electrode material of the embodiment of the present application can be used as an active substance or additive in a zinc-based battery, a lithium-ion battery or a sodium-ion battery to improve battery performance.

[0038] In the embodiment of the present application, the battery is a zinc-based battery, and the electrolyte is an aqueous acidic, neutral or alkaline electrolyte. Aqueous batteries have the advantages of high safety, low cost and high rate.

[0039] The battery of the embodiment of the present application has the characteristics of high safety, low cost and high rate. It can be prepared into terminal portable device batteries, vehicle-mounted power batteries, large-scale energy storage batteries, etc. according to needs and applied to portable terminal devices, electric vehicles, large-scale energy storage, etc., among which the main scenarios of large-scale energy storage include short-term backup power scenarios of data centers, site energy backup power systems, smart photovoltaic energy storage power stations, etc.

[0040] The embodiment of the present application also provides an electric device, the electric device includes an electric component and a power supply component, the power supply component supplies power to the electric component, and the power supply component includes the battery described in the third aspect of the embodiment of the present application. The electric device can be a portable terminal device, an electric car, etc.

[0041] The embodiment of the present application also provides an energy storage system, the energy storage system includes the battery described in the third aspect of the embodiment of the present application. The energy storage system can be an electric vehicle energy storage system, a data center short-term backup power system, a site energy backup power system, an intelligent photovoltaic energy storage power station, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1A schematic diagram of the cross-sectional structure of a zinc-based negative electrode material secondary particle 100 provided in an embodiment of the present application;

[0043] Figure 2 The rate discharge curve of the micron-sized spherical zinc-based negative electrode material C / Bi / ZnO of Example 1 of the present application;

[0044] Figure 3 This is the rate discharge curve of the micron-sized spherical structure C / ZnO negative electrode material of Comparative Example 6 of the present application;

[0045] Figure 4 This is the rate discharge curve of the nano ZnO negative electrode material of Comparative Example 1 of the present application;

[0046] Figure 5 It is a comparison chart of the in-situ corrosion pressure change (hydrogen evolution amount) of the micron-sized spherical structure zinc-based negative electrode material C / Bi / ZnO of Example 1, the micron-sized spherical structure negative electrode material C / ZnO of Comparative Example 6, and the nano ZnO negative electrode material of Comparative Example 1;

[0047] Figure 6 The cycle curve of the micron-sized spherical zinc-based negative electrode material C / Bi / ZnO of Example 1 of the present application;

[0048] Figure 7 This is the cycle curve of the nano ZnO negative electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0049] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0050] The commonly used positive electrode material for alkaline Ni-Zn batteries is Ni(OH) 2 The negative electrode material is a Zn / ZnO mixture or a Zn-based material such as calcium zincate. Since the electrolyte is a high concentration (6-7 mol / L) KOH solution, and the Zn-based negative electrode undergoes a solid-liquid-solid phase (Zn-[Zn(OH) 4 ] 2- -ZnO), so the Zn-based negative electrode inevitably has problems such as corrosion, hydrogen evolution, deformation passivation, and dendrite growth during storage and charge and discharge.

[0051] In order to alleviate the side reactions of the Zn negative electrode, the industry currently usually performs surface modification or doping modification on the zinc negative electrode. Among them, surface coating can reduce the contact between the active material and the electrolyte, improve the problems of zinc negative electrode dendrites and electrode deformation, but most of the current coating strategies use physical confinement to confine the zinc negative electrode to the shell, but the blocking effect on the hydroxyl zinc ions generated during the reaction is minimal, and the inhibition effect on dendrites and corrosion hydrogen evolution is limited. In addition, the structure is usually loose and the tap density is low, making it difficult to achieve low compaction density and high loading of the electrode. In addition to surface coating and modification of the zinc negative electrode, adding metals or metal oxides with high hydrogen evolution overpotential to the main material of the negative electrode to inhibit hydrogen evolution and gas production is another common solution strategy, but simple mechanical addition can easily cause the additives dispersed on the surface of the negative electrode to aggregate and deposit at the bottom during the cycle, losing the protective effect on the upper part of the electrode. In order to effectively improve the side reactions of the zinc negative electrode and ensure that the zinc negative electrode sheet has a high compaction density and negative electrode material loading, an embodiment of the present application provides a negative electrode material, specifically a zinc-based negative electrode material, which is used for aqueous zinc-based batteries and can improve the electrochemical performance of aqueous zinc-based batteries.

[0052] See also Figure 1 , Figure 1 This is a schematic diagram of the cross-sectional structure of a zinc-based negative electrode material provided in an embodiment of the present application, wherein the zinc-based negative electrode material includes secondary particles 100, wherein the secondary particles 100 include a plurality of stacked zinc oxide primary particles 101, and carbon materials 102 dispersed in the secondary particles 100, and metals and / or metal oxides 103.

[0053] In the embodiment of the present application, the carbon material 102 may be amorphous carbon, and the metal and / or metal oxide 103 may be in the form of particles distributed in the secondary particles, or in the form of amorphous state distributed in the secondary particles, depending on their specific types.

[0054] The zinc-based negative electrode material provided in the embodiment of the present application is formed by secondary granulation of zinc oxide primary particles with carbon materials, and metals and / or metal oxides to form micron-sized secondary particles, in which zinc oxide, carbon materials, and metals and / or metal oxides are uniformly distributed and tightly combined, wherein the carbon materials can not only improve the overall conductivity of the secondary particles of the zinc-based negative electrode material, but also improve the compactness and structural stability of the secondary particles; the metals and metal oxides can effectively contact the zinc oxide on the surface and inside of the secondary particles, thereby effectively inhibiting hydrogen evolution and reducing gas production; the zinc-based negative electrode material is better alleviated by the combination of physical confinement and chemical inhibition through secondary granulation, and the corrosion, hydrogen evolution and deformation passivation of the surface of the zinc-based negative electrode during storage and charging and discharging. The zinc-based negative electrode material is used for aqueous zinc-based batteries, which can improve the electrochemical performance of aqueous zinc-based batteries; specifically, physical confinement refers to the formation of a certain coating effect on the surface of the zinc oxide primary particles by the carbon material, which to a certain extent blocks the long-term contact between the electrolyte and zinc oxide, and at the same time, the Zn(OH) generated during the discharge process is 4 2- Compounds such as Bi are confined inside the particles; chemical inhibition refers to increasing the hydrogen evolution overpotential of the material and slowing down hydrogen evolution and gas production by adding metals such as Bi or their metal oxides.

[0055] In the embodiment of the present application, the carbon material 102 and the metal and / or metal oxide 103 are dispersed throughout the secondary particles 100. That is, in any local position of the secondary particles, the carbon material and the metal and / or metal oxide are dispersedly distributed, rather than being concentrated in a certain part of the secondary particles in a specific manner. In other words, in the entire secondary particles, the zinc oxide primary particles, the carbon material, and the metal and / or metal oxide are randomly mixed and distributed.

[0056] In the embodiment of the present application, the metal in the secondary particle 100 may be one or more of Bi, Cu, Sb, Sn, Ag, and In. The metal oxide may be one or more of Bi oxide, Cu oxide, Sb oxide, Sn oxide, Ag oxide, and In oxide. The above-mentioned types of metals have a higher hydrogen evolution overpotential, so that the corrosion and hydrogen evolution of the zinc negative electrode can be better suppressed. It can be understood that the higher the hydrogen evolution overpotential of the metal element contained in the above-mentioned metals and metal oxides, the more conducive it is to suppress the corrosion and hydrogen evolution of the zinc negative electrode.

[0057] In the embodiment of the present application, the secondary particles 100 may include only one or more metals of Bi, Cu, Sb, Sn, Ag, and In, or may include only one or more metal oxides of Bi oxide, Cu oxide, Sb oxide, Sn oxide, Ag oxide, and In oxide. It may also contain one or more metals of Bi, Cu, Sb, Sn, Ag, and In, and one or more metal oxides of Bi oxide, Cu oxide, Sb oxide, Sn oxide, Ag oxide, and In oxide.

[0058] In the embodiment of the present application, when the secondary particle 100 contains both metal and metal oxide, the metal element in the metal oxide and the metal element in the metal may be the same element. For example, the secondary particle 100 contains both metal Bi and Bi oxide.

[0059] In the embodiment of the present application, the total mass proportion of the plurality of zinc oxide primary particles 101 in the secondary particles 100 is greater than 85%. In some embodiments, the total mass proportion of the plurality of zinc oxide primary particles 101 in the secondary particles 100 may be, for example, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%.

[0060] In the embodiment of the present application, in the secondary particles 100, the total mass proportion of the carbon material 102 and the metal and / or metal oxide 103 is less than 10%. In some embodiments, in the secondary particles 100, the total mass proportion of the carbon material and the metal and / or metal oxide is 1%-9.5%. In some embodiments, in the secondary particles 100, the total mass proportion of the carbon material and the metal and / or metal oxide is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5%. In the secondary particles 100, zinc oxide is the main material, and the carbon material, metal and metal oxide are used as auxiliary materials to improve the performance. The addition of carbon material can improve the structural stability of the secondary particles and the conductivity of the secondary particles. The total mass proportion of carbon material, metal and metal oxide is controlled to a suitable small proportion, which can better utilize carbon material and metal or metal oxide to alleviate the side reaction of the zinc negative electrode, improve the structural stability and cycle performance of the negative electrode material, and better ensure that the zinc negative electrode has a higher gram capacity.

[0061] In some embodiments of the present application, in the secondary particles 100, the carbon material 102 is 3%-10% of the mass of zinc oxide. In some embodiments, in the secondary particles 100, the carbon material 102 is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the mass of zinc oxide. The addition of suitable carbon materials is conducive to the carbon materials blocking the contact between the electrolyte and zinc oxide through physical confinement, effectively inhibiting the generation of side reactions; it is also conducive to improving the overall conductivity of the secondary particles, while ensuring that the secondary particles as a whole have a higher gram capacity.

[0062] In the embodiment of the present application, in the secondary particles 100, the molar ratio of the metal and metal oxide to zinc oxide is greater than 0 and less than 0.03. In some embodiments, in the secondary particles 100, the molar ratio of the metal and metal oxide to zinc oxide is 0.001 to 0.03. For example, in the secondary particles 100, the molar ratio of the metal and metal oxide to zinc oxide is 0.001, 0.005, 0.009, 0.01, 0.015, 0.02, 0.025, 0.03. The addition of appropriate amounts of metals and metal oxides can increase the hydrogen evolution overpotential of the secondary particles through the chemical inhibition of the metals and metal oxides, and slow down the hydrogen evolution and gas production.

[0063] In an embodiment of the present application, the particle size D50 of the zinc oxide primary particles 101 is 20nm-500nm. In some embodiments, the particle size D50 of the zinc oxide primary particles 101 is 20nm-300nm. In some embodiments, the particle size D50 of the zinc oxide primary particles 101 is 20nm-100nm. In some embodiments, the particle size D50 of the zinc oxide primary particles 101 is 20nm-50nm. Specifically, in some embodiments, the particle size D50 of the zinc oxide primary particles 101 is 20nm, 25nm, 30nm, 35nm, 40nm, 50nm, 60nm, 80nm, 100nm, 120nm, 130nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm. The zinc oxide primary particles have a smaller particle size, which is conducive to close stacking into secondary particles.

[0064] In the embodiment of the present application, the secondary particles 100 further contain a binder ( Figure 1(not shown), the binder is present in the secondary particles and is dispersed. The addition of the binder is beneficial to strengthen the bonding between the same component particles and different component materials in the secondary particles, reduce the porosity of the secondary particles, and increase the gram capacity of the secondary particles. In the present application, the binder can be one or more of sodium carboxymethyl cellulose CMC, polyvinyl alcohol PVA, cellulose, sodium polyacrylate, polyacrylic acid, and sodium alginate. Among them, in the secondary particles 100, the mass of the binder can be less than 3% of the mass of the zinc oxide primary particles. In some embodiments, in the secondary particles 100, the mass of the binder is 0.5%-2.9% of the mass of the zinc oxide primary particles; specifically, for example, it can be 0.5%, 1%, 1.5%, 1.8%, 2%, 2.5%, 2.9%. The addition of an appropriate amount of binder can better bind the zinc oxide primary particles, carbon materials, metals and metal oxides together more tightly, and at the same time help to ensure that the secondary particles have a higher capacity.

[0065] In the embodiment of the present application, the secondary particles 100 are spherical or quasi-spherical particles. The spherical or quasi-spherical particles have a compact structure and can improve the tap density. In the present application, the particle size D50 of the secondary particles 100 can be 2μm-20μm. In some embodiments, the particle size D50 of the secondary particles 100 can be, for example, 2μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm. Secondary particles of micron size suitable for particle size are conducive to obtaining a suitable specific surface area and ensuring that the negative electrode sheet has a large compaction density.

[0066] In the embodiment of the present application, in the secondary particles 100, the zinc oxide primary particles 101 are tightly combined with the carbon material 102, the metal and / or the metal oxide 103, and the pores in the secondary particles 100 have a pore size of less than 5 nm. In some embodiments, the pores in the secondary particles 100 have a pore size of less than 4 nm. In some embodiments, the pores in the secondary particles 100 have a pore size of less than 3 nm. In some embodiments, the pores in the secondary particles 100 have a pore size of less than 2 nm. The secondary particles formed by the close accumulation of the components have small pores inside, so that the prepared battery negative electrode sheet has a high compaction density and a high active material loading, thereby increasing the battery capacity and the volume energy density of the battery, which is conducive to the battery to achieve a smaller size design.

[0067] In the embodiment of the present application, the specific surface area of ​​the secondary particles 100 is less than 5m 2 In some embodiments, the specific surface area of ​​the secondary particles 100 is less than 4 m 2 In some embodiments, the specific surface area of ​​the secondary particles 100 is less than 3 m 2 In some embodiments, the specific surface area of ​​the secondary particles 100 is less than 2 m 2 / g. The smaller specific surface area of ​​the secondary particles is beneficial to alleviate the excessive side reaction between the material particle surface and the electrolyte.

[0068] In the embodiment of the present application, the specific surface area of ​​the zinc oxide primary particles is about 15 m 2 / g-25m 2 In some embodiments, the specific surface area of ​​the zinc oxide primary particles is about 15 m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 25m 2 / g. The zinc oxide primary particles have a suitable specific surface area, which is conducive to the formation of micron-sized secondary particles with a low specific surface area.

[0069] In the embodiment of the present application, the porosity of the secondary particles 100 is less than 35%. In some embodiments, the porosity of the secondary particles is less than 30%. In some embodiments, the porosity of the secondary particles is less than 25%. In some embodiments, the porosity of the secondary particles is less than 20%. In some embodiments, the porosity of the secondary particles is less than 15%. In some embodiments, the porosity of the secondary particles is less than 10%. The secondary particles having a smaller porosity are beneficial to improving the compaction density and negative electrode material loading of the battery negative electrode sheet, thereby improving the capacity of the battery.

[0070] In the embodiment of the present application, the tap density of the secondary particles 100 is 1.3 g / cm 3 -2.0g / cm 3 In some embodiments, the tap density of the secondary particles 100 is 1.3 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 The secondary particles have a higher tap density, which can increase the active material loading of the battery negative electrode and improve the capacity of the battery.

[0071] The zinc-based negative electrode material provided in the embodiment of the present application can be used in a battery system, such as an aqueous zinc-based battery, to improve the electrochemical performance of the aqueous zinc-based battery. The zinc-based negative electrode material provided in the embodiment of the present application can also be used in the field of photocatalytic hydrogen production from water, the field of heterojunction diode materials for solar cells, and the like. If applied to the field of photocatalytic hydrogen production from water, the zinc-based negative electrode material may be mixed with other semiconductor materials (such as titanium dioxide, etc.) as an additive, and a hydrogen evolution catalyst may be added to construct a composite electrode material; if used to prepare a diode material, the material may be processed and modified, and a heterojunction diode may be constructed using n-type ZnO material and p-type semiconductor material.

[0072] In the embodiment of the present application, the zinc-based negative electrode material may be subjected to scanning electron microscope (SEM) and X-ray energy spectrum (EDS) analysis to obtain the particle size, surface element composition, content and distribution of the material; the zinc-based negative electrode material may be subjected to focused ion beam-electron beam double beam microscope (FIB-SEM) analysis to obtain the cross-sectional element composition, content and distribution of the material; the zinc-based negative electrode material may be subjected to BET nitrogen adsorption and desorption analysis to obtain the material specific surface area, porosity and pore size distribution data; the zinc-based negative electrode material may be subjected to inductively coupled plasma spectroscopy (ICP) analysis to obtain the element composition and specific content of the material.

[0073] The present application also provides a method for preparing a zinc-based negative electrode material, comprising:

[0074] Step 101, mixing a carbon source, a soluble metal salt, zinc oxide primary particles and water to obtain a solid-liquid mixture;

[0075] Step 102: spray-dry and granulate the solid-liquid mixture, and then calcine it under a protective atmosphere to obtain a zinc-based negative electrode material; the zinc-based negative electrode material includes secondary particles, and the secondary particles include a plurality of stacked zinc oxide primary particles, and carbon materials and metals and / or metal oxides dispersed in the secondary particles.

[0076] The preparation method of the embodiment of the present application sprays and granulates a solid-liquid mixture containing a carbon source, a soluble metal salt and zinc oxide primary particles, and obtains secondary particles after calcination. The zinc oxide primary particles, carbon materials and metal particles are evenly dispersed and distributed in the secondary particles and are tightly combined with each other, so as to obtain secondary particles with a smaller specific surface area, thereby better and more effectively inhibiting corrosion, hydrogen evolution and deformation passivation on the surface of the zinc-based negative electrode during storage and charge and discharge, increasing the compaction density of the negative electrode sheet, and thus improving the battery cycle performance and capacity; and the confinement effect of the carbon material in the secondary particles can improve the overall structural stability of the secondary particles; the preparation method is simple and controllable, and can be used for large-scale production.

[0077] In step 101, the carbon source can be various organic carbon sources that can be carbonized to form amorphous carbon, and the organic carbon source can be a soluble organic carbon source, which is conducive to obtaining a uniform solid-liquid mixture of zinc oxide, carbon material and soluble metal salt. The organic carbon source can be, for example, a mixture of one or more of glucose, starch, sucrose, melamine, dopamine, tannic acid, polyvinyl pyrrolidone, citric acid, polyvinyl alcohol, and polypyrrole. The above-mentioned organic carbon source is simple and easy to obtain, and it is easy to achieve complete carbonization.

[0078] In the embodiment of the present application, the soluble metal salt may be one or more of sulfate, nitrate, chloride and acetate. It is understandable that the sulfate may be a sulfate of Bi, a sulfate of Cu, a sulfate of Sb, a sulfate of Sn, a sulfate of Ag, and a sulfate of In; the nitrate may be a nitrate of Bi, a nitrate of Cu, a nitrate of Sb, a nitrate of Sn, a nitrate of Ag, and a nitrate of In; the chloride may be a chloride of Bi, a chloride of Cu, a chloride of Sb, a chloride of Sn, a chloride of Ag, and a chloride of In; the acetate may be an acetate of Bi, an acetate of Cu, an acetate of Sb, an acetate of Sn, an acetate of Ag, and an acetate of In. The above soluble metal salts are readily available and easily dissolved in water. It can be understood that the soluble metal salt can be a soluble salt of a corresponding metal selected according to the metal or metal oxide contained in the pre-designed secondary particles. For example, if the secondary particles need to contain Bi, the soluble metal salt in step 101 is selected from one or more of Bi sulfate, Bi nitrate, Bi chloride, and Bi acetate. The soluble metal salt can be dissolved in water to prepare a salt solution with a concentration of greater than 0 to less than or equal to 3.0 mol / L, and then mixed with the carbon source and the zinc oxide primary particles.

[0079] In the embodiment of the present application, the particle size of the zinc oxide primary particles is as described above and will not be repeated here.

[0080] In some embodiments of the present application, the molar ratio of the soluble metal salt to zinc oxide can be greater than 0 and less than 3%. In some embodiments, the molar ratio of the soluble metal salt to zinc oxide can be 0.5%, 0.9%, 1%, 1.5%, 2%, 2.5%, or 3%.

[0081] In some embodiments of the present application, the mass ratio of the carbon source to zinc oxide is 3%-10%. In some embodiments, the mass ratio of the carbon source to zinc oxide is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0082] In some embodiments of the present application, the solid-liquid mixture also includes a binder. The selection of the binder is as described above and will not be repeated here. The mass of the binder may be less than 3% of the mass of the zinc oxide primary particles. In some embodiments, the mass of the binder is 0.5%-2.9% of the mass of the zinc oxide primary particles; specifically, for example, it may be 0.5%, 1%, 1.5%, 1.8%, 2%, 2.5%, 2.9%.

[0083] In the embodiment of the present application, the solid-liquid ratio in the solid-liquid mixture is 1: (2-5) kg / L. In some embodiments, the solid-liquid ratio in the solid-liquid mixture is 1: 2 kg / L. In some embodiments, the solid-liquid ratio in the solid-liquid mixture is 1: 3 kg / L. In some embodiments, the solid-liquid ratio in the solid-liquid mixture is 1: 4 kg / L. In some embodiments, the solid-liquid ratio in the solid-liquid mixture is 1: 5 kg / L. Suitable control of the solid-liquid ratio is beneficial to controlling the viscosity of the solid-liquid mixture, and is beneficial to preparing secondary particles with a compact structure in the subsequent spray drying process.

[0084] In step 102, the inlet air temperature of the spray drying is 170°C-220°C, and the feed rate is 5mL / min-20mL / min. In some embodiments, the inlet air temperature may be, for example, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C. In some embodiments, the feed rate may be, for example, 5mL / min, 8mL / min, 10mL / min, 12mL / min, 15mL / min, 18mL / min, 20mL / min.

[0085] In the embodiment of the present application, the calcination temperature is 400°C-1000°C. In some embodiments, the calcination temperature may be, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C. The calcination time may be 1h-8h, for example, 1h, 3h, 5h, 6h, 8h. During the calcination process, the heating rate may be controlled to be 2°C / min-8°C / min, for example, 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min. Calcination is carried out under a protective atmosphere, which may be a mixed atmosphere of one or more of nitrogen, argon, and hydrogen. By controlling the inlet air temperature, feed rate, and calcination temperature of the spray drying in a suitable range, compactly packed micron-sized spherical secondary particles with low specific surface area and low porosity can be better obtained.

[0086] In the embodiment of the present application, the zinc oxide primary particles can be prepared by the following method:

[0087] A zinc oxide precursor is prepared by a precipitation method after mixing a zinc metal soluble salt and an alkali, and zinc oxide primary particles are obtained after calcination.

[0088] Wherein, the alkali can be a mixture of one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide. The stoichiometric ratio of the mixture of zinc metal soluble salt and alkali can be 1.8-2.2:1, and the pH after mixing is 7-11, and specifically, for example, the pH can be 7, 8, 9, 10, 11. Wherein, the reaction temperature of the precipitation method is 40°C-80°C, and the reaction time is 0.1h-6h. In some embodiments, the reaction temperature can be 40°C, 50°C, 60°C, 70°C, 80°C; the reaction time can be 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h.

[0089] The embodiment of the present application also provides a battery negative electrode sheet, which includes a current collector and a negative electrode active layer arranged on the current collector, and the negative electrode active layer includes the zinc-based negative electrode material mentioned above in the embodiment of the present application.

[0090] In the embodiment of the present application, the current collector may be, but is not limited to, a copper mesh or copper foam. The negative electrode active layer may include only the zinc-based negative electrode material described in the embodiment of the present application, or may include the zinc-based negative electrode material described in the embodiment of the present application and other negative electrode materials. For zinc-based batteries, other negative electrode materials may be, for example, a Zn / ZnO mixture, calcium zincate, etc. The negative electrode active layer also includes a binder and a conductive agent.

[0091] In the embodiment of the present application, the compaction density of the negative electrode sheet of the battery is greater than or equal to 3.8 g / cm 3 In some embodiments, the compaction density of the negative electrode sheet of the battery is 3.8 g / cm 3 -4.2g / cm3 In some embodiments, the compaction density of the negative electrode sheet of the battery is 3.8 g / cm 3 、3.9g / cm 3 , 4.0g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 In the embodiment of the present application, the zinc-based negative electrode material loading of the battery negative electrode sheet is greater than or equal to 115 mg / cm 2 In some embodiments, the zinc-based negative electrode material loading of the battery negative electrode sheet is 115 mg / cm 2 -125mg / cm 2 In some embodiments, the zinc-based negative electrode material loading of the battery negative electrode sheet is 115 mg / cm 2 、118mg / cm 2 、120mg / cm 2 、123mg / cm 2 , 125mg / cm 2 The negative electrode sheet of the battery in the embodiment of the present application adopts the zinc-based negative electrode material provided above, and has a high compaction density and a high zinc-based negative electrode material loading, which can ensure the high energy density of the battery.

[0092] The embodiment of the present application also provides a battery, which includes a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet includes the battery negative electrode sheet described above in the embodiment of the present application.

[0093] In the embodiment of the present application, the battery may include a zinc-based battery, a lithium-ion battery or a sodium-ion battery. The zinc-based negative electrode material of the embodiment of the present application may be used as an active substance or additive in a zinc-based battery, a lithium-ion battery or a sodium-ion battery to improve battery performance.

[0094] In the embodiment of the present application, the battery may be a zinc-based battery, and the electrolyte may be an aqueous acidic, neutral or alkaline electrolyte. Aqueous batteries have the advantages of high safety, low cost and high rate. The positive electrode of the zinc-based battery may be Ni(OH) 2 As positive electrode active material.

[0095] The battery of the embodiment of the present application may be a soft pack battery, a cylindrical battery, a square shell battery, etc. A plurality of batteries may be connected in series and parallel to form a battery module, and a plurality of battery modules and a battery management system may be packaged to form a battery pack.

[0096] The battery of the embodiment of the present application has the characteristics of high safety, low cost and high rate. It can be prepared into terminal portable device batteries, vehicle-mounted power batteries, large-scale energy storage batteries, etc. according to needs and applied to portable terminal devices, electric vehicles, large-scale energy storage, etc., among which the main scenarios of large-scale energy storage include short-term backup power scenarios of data centers, site energy backup power systems, smart photovoltaic energy storage power stations, etc.

[0097] The embodiment of the present application also provides an electric device, which includes an electric component and a power supply component, the power supply component supplies power to the electric component, and the power supply component includes the battery described in the embodiment of the present application. The electric device can be an electronic device, an electric car, etc., and the electronic device can include a mobile phone, a notebook, a tablet computer, a car computer, a wearable device (such as a watch, a bracelet, glasses), a walkie-talkie, a mobile smart terminal, etc.

[0098] The embodiment of the present application also provides an energy storage system, which includes the battery described above in the embodiment of the present application. Specifically, the energy storage system may include multiple batteries, and the multiple batteries may be connected in series and parallel to form a battery module, and the multiple battery modules and the battery management system may be packaged to form a battery pack. The energy storage system may be an electric vehicle energy storage system, a data center short-term backup power system, a site energy backup power system, an intelligent photovoltaic energy storage power station, etc.

[0099] The embodiments of the present application are further described below with reference to a plurality of embodiments.

[0100] Example 1

[0101] The preparation of secondary particles of zinc-based negative electrode material includes the following steps:

[0102] S1. Preparation of Nano Zinc Oxide Primary Particles:

[0103] S1-1: Use deionized water to remove Zn(NO 3 ) 2 6H 2 O was dissolved to prepare a 2.0 mol / L reaction solution A;

[0104] S1-2: Dissolve KOH in deionized water to prepare a 4.0 mol / L reaction solution B;

[0105] S1-3: Add a small amount of reaction solution B to the reactor, adjust the pH to 9, then uniformly add reaction solution A and reaction solution B while stirring continuously, the stirring speed is 500 rpm / min, the reaction temperature is 50°C, the pH of the reaction system is controlled to be 9.0-9.2, and the reaction time is 1h;

[0106] S1-4: After the reaction is completed, a reaction mixture is obtained, and the reaction mixture is filtered, washed, dried, and calcined at 300° C. for 3 h in an air atmosphere to obtain nano zinc oxide primary particles;

[0107] S2. Preparation of secondary particles of micron-sized spherical zinc-based negative electrode materials:

[0108] S2-1: Weigh 100 g of the nano zinc oxide primary particles prepared in process S1, disperse them into 280 mL of deionized water, and continue stirring;

[0109] S2-2: Weigh 5 g of glucose as a carbon source, 4.5 g of Bi(NO 3 ) 2 ·5H 2 O, stir and dissolve into the above liquid;

[0110] S2-3: Weigh 2 g of CMC (2%) adhesive, stir and disperse it into the above liquid to obtain a solid-liquid mixture;

[0111] S2-4: Under continuous stirring, the solid-liquid mixture obtained in step S2-3 is spray dried, the air inlet temperature is controlled to be 180°C, the feed rate is 10 mL / min, and after the spray liquid is injected, deionized water is injected, and the injection is stopped after about 1 minute, and the precursor solid powder is collected;

[0112] S2-5: In N 2 Under a protective atmosphere, the precursor solid powder obtained in step S2-4 is calcined at 600°C for 2h, and the heating rate is controlled to be 5°C / min. After cooling, micron-sized spherical zinc-based negative electrode material secondary particles C / Bi / ZnO (" / " indicates composite) are obtained. In the zinc-based negative electrode material secondary particles C / Bi / ZnO obtained in this embodiment, the mass of carbon material is 5% of the mass of ZnO, and the molar ratio of metal or metal oxide to ZnO is about 0.9%.

[0113] Preparation of zinc negative electrode: The zinc-based negative electrode material secondary particles C / Bi / ZnO prepared in this embodiment are mixed with metal zinc powder, acetylene black, and PTFE (polytetrafluoroethylene) in a ratio of 70:20:5:5 to form a slurry, coated on the gaps in the brass mesh, and dried in an oven at 80°C for 2 hours to obtain the battery negative electrode sheet used for electrochemical characterization in this embodiment.

[0114] Preparation of nickel-zinc battery: The battery negative electrode sheet prepared in this example is used as the negative electrode, 6M KOH saturated with ZnO is used as the electrolyte, and spherical nickel hydroxide is used as the positive electrode to assemble an alkaline nickel-zinc battery.

[0115] Example 2

[0116] The difference between the preparation of zinc-based negative electrode material secondary particles in this embodiment and that in Example 1 lies in the different solid content in the spray liquid, i.e., the solid-liquid mixture. Specifically, in step S2-1, 100 g of nano zinc oxide primary particles prepared in process S1 are weighed and dispersed in 200 mL of deionized water.

[0117] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0118] Example 3

[0119] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in embodiment 1 is that the Bi(NO 3 ) 3 ·5H 2 O is 9g.

[0120] The zinc-based negative electrode material of Example 3 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0121] Example 4

[0122] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in Embodiment 1 is that 10 g of glucose is added in step S2-2, and the calcination temperature in step S2-5 is 800°C.

[0123] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0124] Example 5

[0125] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in Embodiment 1 is that the zinc oxide primary particles used in step S2-1 are commercial-grade nano zinc oxide powders.

[0126] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0127] Example 6

[0128] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in Embodiment 1 is that the carbon source added in step S2-2 is melamine, and the amount added is 10 g.

[0129] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0130] Example 7

[0131] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in embodiment 1 is that:

[0132] S2: Preparation of secondary particles of micron-sized spherical zinc-based negative electrode materials:

[0133] S2-1: Weigh 100 g of the ZnO powder prepared in the S1 process of Example 1, disperse it into 320 mL of deionized water, and continue stirring;

[0134] S2-2: Weigh 5 g of glucose as a carbon source, 4.5 g of Bi(NO 3 ) 2 ·5H 2 O, stir and dissolve into the above liquid;

[0135] S2-3: Weigh 3 g of PVA (3%) adhesive and disperse it in the above liquid by stirring;

[0136] S2-4: Under continuous stirring, the solid-liquid mixture obtained in step S2-3 was spray dried, the air inlet temperature was controlled to be 180° C., the feed rate was 10 mL / min, after the spray liquid was injected, deionized water was injected, the injection was stopped after about 1 minute, and the precursor solid powder was collected;

[0137] S2-5: In N 2 Under a protective atmosphere, the precursor solid powder obtained in step S2-4 was calcined at 600° C. for 2 h, with the heating rate controlled at 5° C. / min, and after cooling, a micron-sized spherical zinc-based negative electrode material C / Bi / ZnO was obtained.

[0138] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0139] Example 8

[0140] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in embodiment 1 is that the metal soluble salt added in step S2-2 is Cu(NO 3 ) 2 ·3H 2 O, the amount added was 3.5g; finally, the micron-sized spherical structure zinc-based negative electrode material C / Cu / ZnO was prepared.

[0141] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0142] Example 9

[0143] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in embodiment 1 is that the metal soluble salt added in step S2-2 is Sn(CH 3 CO 2 ) 2 , the amount added was 2.0g; finally, a micron-sized spherical structure zinc-based negative electrode material C / Sn / ZnO was prepared.

[0144] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0145] Example 10

[0146] The difference between the preparation of the zinc-based negative electrode material secondary particles in this embodiment and that in embodiment 1 is that the metal soluble salt added in step S2-2 is Sb(CH 3 CO 2 ) 3 , the amount added was 2.5g; finally, a micron-sized spherical structure zinc-based negative electrode material C / Sb / ZnO was prepared.

[0147] The zinc-based negative electrode material of Example 2 is used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0148] Comparative Example 1

[0149] The nano zinc oxide primary particles obtained in step S1 of Example 1 were used as negative electrode active materials to prepare negative electrode sheets and zinc-based batteries in the same manner as in Example 1.

[0150] Comparative Example 2

[0151] The negative electrode sheet and the alkaline nickel-zinc battery were prepared by using commercially available nano zinc oxide negative electrode material as the negative electrode active material, in the same manner as in Example 1.

[0152] Comparative Example 3

[0153] The preparation of nano-scale zinc oxide negative electrode material C / ZnO, the specific steps are as follows:

[0154] S10: Weigh 100 g of ZnO powder prepared in the S1 process of Example 1 and 5 g of glucose as a carbon source, disperse them into 280 mL of deionized water, and continue stirring for 30 min;

[0155] S20: drying in an oven at 100° C. for 12 h, collecting and grinding to obtain a precursor solid powder;

[0156] S30: In N 2Under a protective atmosphere, the precursor solid powder obtained in step S20 is calcined at 600° C. for 2 h, with a heating rate of 5° C. / min, and after cooling, nano-scale zinc oxide negative electrode material C / ZnO primary particles are obtained;

[0157] The C / ZnO zinc oxide negative electrode material of Comparative Example 3 was used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0158] Comparative Example 4

[0159] Preparation of nano-scale zinc oxide negative electrode material Bi / ZnO, which is different from Comparative Example 3 in that no carbon source is added in step S1, but 4.5 g of Bi(NO 3 ) 2 ·5H 2 O; finally, Bi-coated nano-scale zinc oxide negative electrode material Bi / ZnO primary particles are prepared.

[0160] The Bi / ZnO negative electrode material of Comparative Example 4 was used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0161] Comparative Example 5

[0162] Preparation of nano-scale zinc oxide negative electrode material C / Bi / ZnO, which is different from Comparative Example 3 in that 4.5 g of Bi(NO 3 ) 2 ·5H 2 O.

[0163] The C / Bi / ZnO negative electrode material of Comparative Example 5 was used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0164] Comparative Example 6

[0165] The preparation of the C / ZnO negative electrode material with a micron spherical structure in Comparative Example 6 is different from that in Example 1 in that no soluble metal salt is added in step S2.

[0166] The C / ZnO negative electrode material of Comparative Example 6 was used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0167] Comparative Example 7

[0168] The preparation of the micron-spherical ZnO negative electrode material in Comparative Example 7 is different from that in Example 1 in that no carbon source and no metal soluble salt are added in step S2.

[0169] The ZnO negative electrode material of Comparative Example 7 was used as the negative electrode active material to prepare a negative electrode sheet and an alkaline nickel-zinc battery in the same manner as in Example 1.

[0170] The negative electrode active material loading, compaction density, and compaction porosity of the negative electrode sheets of Examples 1 to 10 and Comparative Examples 1 to 7 were calculated or measured, and the results are shown in Table 1; the alkaline nickel-zinc batteries of Examples 1 to 10 and Comparative Examples 1 to 7 were tested for 1C specific capacity, 1C coulomb efficiency, 10C discharge capacity retention rate, and cycle performance, and the results are shown in Table 1.

[0171] Among them, the negative electrode active material loading of the negative electrode sheet can be obtained directly by weighing, the compaction density can be obtained by dividing the loading by the volume of the electrode sheet, the porosity is measured by the BET nitrogen adsorption and desorption test, and the specific capacity, coulombic efficiency and discharge capacity retention rate of the alkaline nickel-zinc battery can all be measured by the Xinwei battery testing system.

[0172] Table 1

[0173]

[0174] From the results in Table 1, it can be seen that the batteries of Examples 1-10 of the present application can be stably cycled for more than 1000 times without dendrites, and the cycle performance is significantly improved relative to the batteries of Comparative Examples 1 to Comparative Examples 7. This is because Examples 1-10 of the present application use zinc-based negative electrode material secondary particles C / Bi / ZnO with special composition and structure as negative electrode active materials to prepare negative electrode sheets, and the negative electrode sheets have high cycle stability. The zinc negative electrode sheets of Examples 1 to 10 of the present application, due to the use of zinc-based negative electrode material secondary particles C / Bi / ZnO with special composition and structure as negative electrode active materials, have significantly improved negative electrode active material loading and compaction density relative to the zinc negative electrode sheets of Comparative Examples 1 to Comparative Examples 5, and significantly reduced compaction porosity. Comparing Example 1 with Comparative Example 5, it can be seen that the present application prepares zinc-based negative electrode material secondary particles in which zinc oxide, carbon material, and metal and / or metal oxide are uniformly distributed and tightly combined by spray drying. The secondary particles are relative to the negative electrode material prepared by the direct solid phase sintering method of Comparative Example 5, which can make the negative electrode sheet have a higher negative electrode active material loading and compaction density, as well as a lower compaction porosity, and ultimately can significantly improve the capacity, coulomb efficiency and cycle performance of the zinc-based battery. Comparing Example 1 with Comparative Example 6, it can be seen that the negative electrode active material loading and compaction density of the negative electrode sheet of Example 1 of the present application are significantly improved, and the cycle performance is significantly improved. Comparing Example 1 with Comparative Example 7, it can be seen that the negative electrode active material loading and compaction density of the negative electrode sheet of Example 1 of the present application are significantly improved, and the cycle performance is significantly improved.

[0175] in addition, Figure 2 The rate discharge curve of the micron-sized spherical zinc-based negative electrode material (C / Bi / ZnO) of Example 1 of the present application; Figure 3 This is the rate discharge curve of the micron-sized spherical structure C / ZnO negative electrode material of Comparative Example 6 of the present application; Figure 4 This is the rate discharge curve of the nano ZnO negative electrode material of comparative example 1 of the present application; Figure 2 , Figure 3 and Figure 4 It can be seen from the results that the micron-sized spherical structure zinc-based negative electrode material (C / Bi / ZnO) of Example 1 of the present application has better rate performance than the micron-sized spherical structure C / ZnO negative electrode material of Comparative Example 6 and the nano ZnO negative electrode material of Comparative Example 1.

[0176] Figure 5 The in-situ corrosion pressure change (hydrogen evolution amount) comparison diagram of the micron-sized spherical structure zinc-based negative electrode material C / Bi / ZnO of Example 1, the micron-sized spherical structure negative electrode material C / ZnO of Comparative Example 6 and the nano ZnO negative electrode material of Comparative Example 1; Figure 5 It can be seen that the amount of hydrogen evolution of the micron-sized spherical structure zinc-based negative electrode material C / Bi / ZnO in Example 1 of the present application is very small, indicating that the micron-sized spherical structure zinc-based negative electrode material C / Bi / ZnO in Example 1 can effectively inhibit hydrogen evolution compared with the micron-sized spherical structure negative electrode material C / ZnO in Comparative Example 6 and the nano ZnO negative electrode material in Comparative Example 1.

[0177] Figure 6 The cycle curve of the micron-sized spherical structure zinc-based negative electrode material (C / Bi / ZnO) of Example 1 of the present application; Figure 7 This is the cycle curve of the nano ZnO negative electrode material of Comparative Example 1. Figure 6 and Figure 7 It can be found that the loosely distributed nano ZnO particles in Comparative Example 1 are severely corroded during the cycle and fail after 200 cycles; while the micron-spherical C / Bi / ZnO negative electrode material of Example 1 of the present application after spray granulation can be cycled more than 1000 times. This is because the conductive network formed by the carbon material is conducive to uniform charge, and the high hydrogen evolution overpotential metal can reduce the hydrogen evolution side reaction.

[0178] in, Figure 2 , Figure 3 , Figure 4 , Figure 6 , Figure 7 It can be obtained through the Xinwei battery testing system test. Figure 5 The battery internal pressure test device can be built.

[0179] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.

[0180] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0181] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0182] In this application, “-” represents a range value, including the endpoint values ​​at both ends. For example, the value of a can be 0.5-15, which means that the value of a can be between 0.5 and 15, and includes the endpoint values ​​0.5 and 15.

[0183] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes secondary particles, which include a plurality of stacked zinc oxide primary particles, and carbon materials dispersed in the secondary particles, and metals and / or metal oxides, wherein the metal includes one or more of Bi, Cu, Sb, Sn, Ag, and In, and the metal oxide includes one or more of Bi oxide, Cu oxide, Sb oxide, Sn oxide, Ag oxide, and In oxide.

2. The negative electrode material according to claim 1, characterized in that The carbon material, and the metal and / or metal oxide are dispersed throughout the secondary particles.

3. The negative electrode material according to claim 1, characterized in that In the secondary particles, the mass proportion of the plurality of zinc oxide primary particles is greater than 85%.

4. The negative electrode material according to claims 1 to 3, characterized in that In the secondary particles, the total mass of the carbon material, the metal and the metal oxide accounts for less than 10%.

5. The negative electrode material according to any one of claims 1 to 4, characterized in that The particle size D50 of the zinc oxide primary particles is 20nm-500nm.

6. The negative electrode material according to any one of claims 1 to 5, characterized in that The secondary particles further contain a binder.

7. The negative electrode material according to claim 6, characterized in that In the secondary particles, the mass of the binder is less than 3% of the mass of the zinc oxide.

8. The negative electrode material according to any one of claims 1 to 7, characterized in that The secondary particles are spherical or quasi-spherical particles.

9. The negative electrode material according to any one of claims 1 to 8, characterized in that The particle size D50 of the secondary particles is 2 μm-20 μm.

10. The negative electrode material according to any one of claims 1 to 9, characterized in that: The zinc oxide primary particles are tightly combined with the carbon material, the metal and / or the metal oxide, and the pores in the secondary particles have a pore size of less than 5 nm.

11. The negative electrode material according to any one of claims 1 to 10, characterized in that The specific surface area of ​​the secondary particles is less than 5m 2 / g.

12. The negative electrode material according to any one of claims 1 to 11, characterized in that The porosity of the secondary particles is less than 35%.

13. The negative electrode material according to any one of claims 1 to 12, characterized in that: The tap density of the secondary particles is 1.3 g / cm 3 -2.0g / cm 3 .

14. A method for preparing a negative electrode material, characterized in that: include: mixing a carbon source, a soluble metal salt, zinc oxide primary particles and water to obtain a solid-liquid mixture; The solid-liquid mixture is spray-dried and granulated, and then calcined under a protective atmosphere to obtain a negative electrode material; the negative electrode material includes secondary particles, the secondary particles include a plurality of stacked zinc oxide primary particles, and carbon materials and metals and / or metal oxides dispersed in the secondary particles, the metal includes one or more of Bi, Cu, Sb, Sn, Ag, and In, and the metal oxide includes one or more of Bi oxide, Cu oxide, Sb oxide, Sn oxide, Ag oxide, and In oxide.

15. The preparation method according to claim 14, characterized in that: The carbon source includes one or more of glucose, starch, sucrose, and citric acid; the soluble metal salt includes one or more of sulfate, nitrate, chloride, and acetate; and the particle size D50 of the zinc oxide primary particles is 20nm-300nm.

16. The preparation method according to claim 14 or 15, characterized in that: The solid-liquid ratio in the solid-liquid mixture is 1:(2-5)kg / L.

17. The preparation method according to any one of claims 14 to 16, characterized in that: The inlet air temperature of the spray drying is 170° C.-220° C., and the feed rate is 5 mL / min-20 mL / min.

18. The preparation method according to any one of claims 14 to 17, characterized in that: The calcination temperature is 400°C-1000°C.

19. A battery negative electrode sheet, characterized in that: The battery negative electrode sheet comprises a current collector and a negative electrode active layer disposed on the current collector, and the negative electrode active layer comprises the negative electrode material according to any one of claims 1 to 13.

20. The battery negative electrode sheet according to claim 19, characterized in that: The compaction density of the negative electrode sheet is greater than or equal to 3.8 g / cm 3 The negative electrode material loading of the negative electrode sheet is greater than or equal to 115 mg / cm 2 .

21. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet comprises the battery negative electrode sheet according to any one of claims 19-20.

22. The battery according to claim 21, characterized in that The battery includes a zinc-based battery, a lithium-ion battery or a sodium-ion battery.

23. The battery according to claim 21, characterized in that The battery is a zinc-based battery, and the electrolyte is an aqueous acidic, neutral or alkaline electrolyte.

24. An electrical equipment, characterized in that: The electrical equipment comprises an electrical component and a power supply component, the power supply component supplies power to the electrical component, and the power supply component comprises the battery according to any one of claims 21-23.

25. An energy storage system, characterized in that: The energy storage system comprises the battery according to any one of claims 21-23.